Selective arc-discharge synthesis of Dy2S-clusterfullerenes and their isomer-dependent single molecule magnetism. Issue 9 (26th July 2017) - Chen, Chia-Hsiang; Krylov, Denis S.; Avdoshenko, Stanislav M.; Liu, Fupin; Spree, Lukas; Yadav, Ravi; Alvertis, Antonis; Hozoi, Liviu; Nenkov, Konstantin; Kostanyan, Aram; Greber, Thomas; Wolter, Anja U. B.; et al.
Abstract : Dy-sulfide clusterfullerene single molecule magnets are synthesized selectively, and their relaxation of magnetization is thoroughly studied by DC and AC-magnetometry. Abstract : A method for the selective synthesis of sulfide clusterfullerenes Dy2 S@C2 n is developed. Addition of methane to the reactive atmosphere reduces the formation of empty fullerenes in the arc-discharge synthesis, whereas the use of Dy2 S3 as a source of metal and sulfur affords sulfide clusterfullerenes as the main fullerene products along with smaller amounts of carbide clusterfullerenes. Two isomers of Dy2 S@C82 with C s (6) and C 3v (8) cage symmetry, Dy2 S@C72 - C s (10528), and a carbide clusterfullerene Dy2 C2 @C82 - C s (6) were isolated. The molecular structure of both Dy2 S@C82 isomers was elucidated by single-crystal X-ray diffraction. SQUID magnetometry demonstrates that all of these clusterfullerenes exhibit hysteresis of magnetization, with Dy2 S@C82 - C 3v (8) being the strongest single molecule magnet in the series. DC- and AC-susceptibility measurements were used to determine magnetization relaxation times in the temperature range from 1.6 K to 70 K. Unprecedented magnetization relaxation dynamics with three consequent Orbach processes and energy barriers of 10.5, 48, and 1232 K are determined for Dy2 S@C82 - C 3v (8). Dy2 S@C82 - C s (6) exhibits faster relaxation of magnetization with two barriers of 15.2 and 523 K. Ab initio calculations were used to interpret experimental data and compare the Dy-sulfide clusterfullerenes to other Dy-clusterfullerenes. The smallest and largest barriers are ascribed to the exchange/dipolar barrier and relaxation via crystal-field states, respectively, whereas an intermediate energy barrier of 48 K in Dy2 S@C82 - C 3v (8) is assigned to the local phonon mode, corresponding to the librational motion of the Dy2 S cluster inside the carbon cage.